Comparative evaluation of indigenous herbal mouthwash with 0.2% chlorhexidine gluconate mouthwash in prevention of plaque and gingivitis: A clinico-microbiological study - Vrushali Ramdas Khobragade; Prashanth Yachrappa Vishwakarma; Arun Suresh Dodamani; Vardhaman Mulchand Jain; Gaurao Vasantrao Mali; Minal Madhukar Kshirsagar (Wolters Kluwer Medknow Publications, 2020)
Background: Plaque control measures are important to maintain proper oral hygiene. Indigenous medicines can be alternatives considered with minimal or no side effects to treat oral diseases. Aim: To determine and compare the antibacterial efficacy of indigenous herbal mouthwash with 0.2% chlorhexidine gluconate. Materials and Methods: The present study was conducted in two parts, and it was registered for the Clinical Trials Registry-India. The first part consisted of in vitro evaluation in which disc diffusion and minimum inhibitory concentration (MIC) methods were used. In the second part, a clinical trial was conducted among 30 participants of 18-40 years' age group to evaluate and compare the antibacterial efficacy of indigenous herbal mouthwash with 0.2% chlorhexidine gluconate. Plaque and gingival health assessments were carried out using the plaque index and gingival index on the 7th day, 14th day, and 21st day. All statistical procedures were performed using the Statistical Package for the Social Sciences 20.0 software (IBM, Armonk, NY, USA). It was assessed at 5% level of significance, i.e., P < 0.05 was considered as statistically significant. Results were statistically analyzed with unpaired t-test for pairwise intergroup multiple comparisons, on the 21st day, when plaque and gingival health were compared using plaque and gingival indices (P < 0.05). Results: Indigenous herbal mouthwash was seen to be sensitive at 12.5 mg/ml, and the zone of inhibition was highest against Prevotella intermedia (23 mm). With 0.2% chlorhexidine gluconate, the zone of inhibition was highest for Porphyromonas gingivalis and Prevotella intermedia (25 mm each) and MIC was seen to be 12.5 mg/ml for Bacteroides forsythus and 0.2 mg/ml for Streptococcus mutans and Lactobacilli by broth technique. In vivo examination showed a decrease in mean scores of plaque index and gingival index with chlorhexidine and indigenous herbal mouthwash from baseline to 21 days. Conclusion: From the present study, it was seen that there was a statistically significant reduction in both clinical and microbiological parameters with the use of an indigenous herbal mouthwash as well as 0.2% chlorhexidine gluconate. However, chlorhexidine mouthwash was statistically efficacious at the 21st day in controlling plaque and gingivitis with potent antimicrobial activity.